Analisis Kepuasan Pelanggan Terhadap Keputusan Pembelian Beras Berlabel - Erwan Erwan; Untari Untari; Ineke Nursih Widyantari (Musamus Journal of Agribusiness, 2021)
This research aims to : 1) know the influence of simultaneous (shared) between the variable of customer satisfaction toward the purchasing decisions, 2) know whether the customer satisfaction are the variables that influence the purchase decision of partially, 3) know the variable of customer satisfaction dominated of the rice purchases labeled. This research was conducted in Toko Dua departement store for five months, from May to September 2013. Analysis used are Linear Regression Multiple, accidental sampling method based on the total sample are 66 respondents. The results showed that the results of the test simultaneous (F) indicating that Fcount (2,824) > Ftable (2,37); so it is concluded the variable of costumer satisfaction simultaneously and significant to affect of the decision to buy. Partial assay results test (t) indicating that variable, among five namely the quality of the product the prices of emotional factors and charges; that significantly affect customers in a decision to buy rice labeled is variable fee; it showed that t count (2,698) > t table (1,669). The results of the test determinan (R) indicating that variable of customer satisfaction having value domination 19,1 % of the decision of the purchase, the remaining 80,9 % influenced by other factors outside of a operation variable.